2020
DOI: 10.1093/gbe/evaa268
|View full text |Cite
|
Sign up to set email alerts
|

Step-by-Step Evolution of Telomeres: Lessons from Yeasts

Abstract: In virtually every eukaryotic species, the ends of nuclear chromosomes are protected by telomeres, nucleoprotein structures counteracting the end-replication problem and suppressing recombination and undue DNA repair. Although in most cases, the primary structure of telomeric DNA is conserved, there are several exceptions to this rule. One is represented by the telomeric repeats of ascomycetous yeasts, which encompass a great variety of sequences, whose evolutionary origin has been puzzling for several decades… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 122 publications
1
31
0
Order By: Relevance
“…Here, we report, for the first time, the telomere sequence and the maximum putative template regions in Toluraspora , using the previously predicted TRs from T. delbrueckii and T. microellipsoides and our own TR predictions for other species of Torulaspora . Our results from Saccharomycetaceae also support some of the putative telomere sequences in comprehensive telomere searches across Ascomycota 23 . Torulaspora delbrueckii and T. microellipsoides are examples of the intrageneric variability of the telomere sequence.…”
Section: Discussionsupporting
confidence: 75%
See 4 more Smart Citations
“…Here, we report, for the first time, the telomere sequence and the maximum putative template regions in Toluraspora , using the previously predicted TRs from T. delbrueckii and T. microellipsoides and our own TR predictions for other species of Torulaspora . Our results from Saccharomycetaceae also support some of the putative telomere sequences in comprehensive telomere searches across Ascomycota 23 . Torulaspora delbrueckii and T. microellipsoides are examples of the intrageneric variability of the telomere sequence.…”
Section: Discussionsupporting
confidence: 75%
“…In the genus Tetrapisispora , until now, the TR was known only in T. blattae (with an unspecified template region) and telomere sequences were found only very recently in three other species of the genus 23 ; we also detected the three published telomere candidates, with 25/28, and 25 nt long motifs, respectively, T. fleetii , T. iriomotensis , and T. namnaoensis . Cervenak et al 23 also showed that T. iriomotensis had telomere motifs 28/29 nucleotides long at the ends of genomic scaffolds. This would make these species record holders in the motif length among Saccharomycetaceae.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations